2018
DOI: 10.4322/acr.2018.051
|View full text |Cite
|
Sign up to set email alerts
|

Late stillbirth due to listeriosis

Abstract: Listeriosis is a sporadic infectious disease, which affects high-risk populations, such as the elderly, pregnant women, newborns, and immunocompromised patients. During pregnancy, listeriosis usually presents like a mild non-specific infection, but it may be responsible for fetal loss, preterm labor, early onset neonatal sepsis, and neonatal death. We report the case of a late stillbirth secondary to maternal chorioamnionitis. Listeria monocytogenes was isolated from the amniotic fluid and the fetal pleural fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The incidence of listeriosis in pregnancy has been described as between 0.7 and 12 cases in 100 000 pregnancies 3 4. Evidence also suggests that ethnicity is a significant risk factor with Asian and Afro-Caribbean pregnant women found to have a higher incidence of listeriosis compared with Caucasians 2.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of listeriosis in pregnancy has been described as between 0.7 and 12 cases in 100 000 pregnancies 3 4. Evidence also suggests that ethnicity is a significant risk factor with Asian and Afro-Caribbean pregnant women found to have a higher incidence of listeriosis compared with Caucasians 2.…”
Section: Discussionmentioning
confidence: 99%
“…However, the complication can be represented by preterm birth, early-onset neonatal sepsis and fetal loss [27]. Segado-Arenas et al ( 2018) reported a case of a late stillbirth secondary to maternal chorioamnionitis [51].…”
Section: Listeria Monocytogenesmentioning
confidence: 99%
“…During pregnancy, listeriosis usually only presents with fever and flu-like symptoms, such as fatigue and myalgia. However, the complication of infections during pregnancy include miscarriage, stillbirth, premature delivery, or lifethreatening neonatal sepsis and fetal loss [2].…”
Section: Introductionmentioning
confidence: 99%